PENGARUH ROA, DER TERHADAP NILAI PERUSAHAN SUBSEKTOR KONSTRUKSI DAN BANGUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dimas Pratama Putra; Syahyuni Syahyuni (Jurnal RATRI (Riset Akuntansi Tridinanti), 2022)
This study aims to determine how financial performance can affect firm value in the construction and building subsector listed on the IDX. This research is important to know how much influence the company's financial condition has during unstable world economic conditions. The method used in this research is descriptive quantitative. Collecting data used in this study by using the documentation method, namely data from financial statements listed on the IDX. The results of this study indicate that H1 is accepted so that it can be concluded that Return On Assets (ROA), Debt To Equity Ratio (DER) simultaneously have an effect on Firm Value, H2 is accepted so that Return On Assets (ROA) partially has a significant positive effect on Firm Value, and H3 is rejected so that the Debt To Equity Ratio (DER) partially does not have a significant effect on firm value in construction and building sub-sector companies listed on the IDX.Kata Kunci : ROA, DER, Firm Value